Mercury distribution, bioaccumulation and risk assessment in different climate areas in the North Atlantic Ocean - Vieira, Hugo Miguel Coelho da Silva (2021)
Mercury (Hg) is classified as a priority hazardous substance by the Convention for the Protection of the Marine Environment of the North-East Atlantic (OSPAR Convention), the European Union Water Framework Directive (EU-WFD) due to the combination of its frequency, toxicity and potential effects on human health and wildlife. In the environment, Hg can be converted into other forms of Hg (e.g. methylmercury – MeHg). MeHg is a potent neurotoxin, which can accumulate in the organism’s tissues due to its high rate of absorption by the gastrointestinal tract and its affinity for thiol groups of proteins. The human exposure to Hg occurs mainly through the consumption of fish. Despite being essential for a healthy balanced diet owing to a high content of protein and fatty acids, fish ingestion can result in the intake of large amounts of Hg since some species have high Hg levels in their tissues. Thus, this study presents as central question the evaluation of the distribution, bioaccumulation and exposure to Hg in different geographic areas located in the North Atlantic (Portuguese northwest coast, Azores archipelago and Mexican southwest coast). In this sense, the following specific objectives were outlined: (i) to determine the presence of Hg in the sediment of coastal areas from different geographic areas; (ii) to evaluate a potential transfer of the Hg present in the sediment to the marine food chain; (iii) to assess the effect of different sea water temperature scenarios on the bioaccumulation and toxicity of the Hg; (iv) to evaluate the [Hg] present in marine species of commercial interest in the different coastal areas (fish and squid) and (v) to understand the contribution of each species to human exposure to Hg. The results revealed that the Hg concentration in the sediments in the different areas reflect the proximity to possible sources of contamination by Hg. The fine fraction is the one with the higher levels of Hg when compared to the fraction of coarser sediments (sand). However, although in some places these Hg levels exceed the values established by international agencies through the criteria for the quality of sediments, the fine fraction represents less than 1% of the total sediment fraction. Therefore, the Hg concentration present in the total sediment fraction was found to be below the limits established by the different agencies. Regarding the transfer of Hg from sediments to the marine trophic chain, the results showed that levels of Hg present in the studied species do not seem to be related to the transfer of Hg present in sediments, but rather to the ingestion of Hg through food. abstract (cont.) This study also concludes that even in a short-term exposure to low Hg concentrations, the increase of water temperature can promote the Hg accumulation in fish. The accumulation was is most evident in the liver. This increase in the Hg concentration in tissues, as well as the increase of water temperature, can induce the production of reactive oxygen species (ROS) by the organisms. However, the antioxidant defenses of the liver seem to act efficiently in combating these ROS, preventing cells damage by oxidative stress. On the other hand, in the muscle, the fight against ROS was not so efficient resulting in damage at the proteins’ level and decreased energy consumption. Regarding the Hg concentration in different fish species with commercial value, it was observed that characteristics such as feeding habits and lifestyle, have an influence on Hg accumulation. Carnivorous fish species are those that have higher concentrations of Hg, which reinforces the notion that Hg can biomagnify along the food chain. Finally, considering the Hg accumulation in the different species of commercial interest and the maximum limit of Hg allowed for human consumption (of 0.5 µg g-1 ), only two fish species (Mora moro and Zeus faber) showed a Hg concentration above this limit. Despite this, consumption of 14 of the studied fish species may lead to a weekly intake of Hg greater than 1.3 µg kg body weight-1 week-1 suggested by JECFA (Joint FAO/WHO Expert Committee on Food Additives). From these 14 species, 9 concern the Azores archipelago and 4 the Northwest Portuguese coast, which are areas with a fish consumption per capita estimated by the FAO three times higher than the southeast coast of Mexico. In fact, data from the Azores archipelago demonstrated that the species that contributed the most to human exposure in this area were those that presented low Hg concentration but were captured in larger quantities. Even though Hg is a widely studied contaminant, the results obtained in the framework of this thesis allowed us to obtain knowledge regarding the presence of Hg in the North Atlantic coastal areas that provide multiple ecosystem services and have until now been poorly studied. It also contributes to the state of the art regarding human exposure to Hg through the consumption of fish and seafood in risk analysis, since Hg concentration usually receives greater importance regardless of the fish consumption per capita.